Seventeen years of subcutaneous infection by Aspergillus flavus; eumycetoma confirmed by immunohistochemistry. Issue 12 (26th October 2015) - Ahmed, Sarah A.; Abbas, Manal A.; Jouvion, Gregory; Al‐Hatmi, Abdullah M. S.; de Hoog, G. Sybren; Kolecka, Anna; Mahgoub, El Sheikh
Summary: Chronic subcutaneous infections caused by Aspergillus species are considered to be extremely rare. Because these fungi are among the most common laboratory contaminants, their role as eumycetoma causative agents is difficult to ascertain. Here, we report the first case of A. flavus eumycetoma confirmed by isolation, molecular identification and immunohistochemical analysis. Patient was a 55‐year‐old male from Sudan suffering from eumycetoma on his left foot for a period of 17 years. He developed swelling, sinuses and white grain discharge was observed. He has been operated nine times and was treated with several regimens of ketoconazole and itraconazole without improvement. Initial diagnosis based on histology and radiology was Scedosporium eumycetoma. However, examination of the biopsy revealed A. flavus, which was identified by molecular analysis and MALDI‐TOF MS. Immunohistochemistry using antibody directed against Aspergillus species was positive. Because of the earlier treatment failures with ketoconazole and itraconazole, therapy with voriconazole was initiated. However, in vitro susceptibility testing yielded a lower Minimum Inhibitory Concentration (MIC) value for itraconazole (0.25 μg ml −1 ) than for voriconazole (1 μg ml −1 ). Based on the presented results, A. flavus can be considered as one of the agents of white‐grain eumycetoma.